The platelet receptor CLEC-2 is active as a dimer - Watson, A.; Christou, C.; James, J.; Fenton-May, A.; Moncayo, G.; Mistry, A.; Davis, S.; Gilbert, R.; Chakera, Aron; O'Callaghan, C. (American Chemical Society, 2009)
The platelet receptor CLEC-2 binds to the snake venom toxin rhodocytin and the tumor cell surface protein podoplanin. Binding of either of these ligands promotes phosphorylation of a single tyrosine residue in the YXXL motif in the intracellular domain of CLEC-2. Phosphorylation of this tyrosine initiates binding of spleen tyrosine kinase (Syk) and triggers further downstream signaling events and ultimately potent platelet activation and aggregation. However, it is unclear how a single YXXL motif can interact efficiently with Syk, which usually recognizes two tandem YXXL repeats presented as an immunoreceptor tyrosine-based activation motif (ITAM). Using bioluminescence resonance energy transfer, coimmuno-preciptitation, recombinant protein expression and analytical gel filtration chromatography, surface plasmon resonance, Western blotting, multiangle light scattering (MALS), and analytical ultracentrifugation, we show that CLEC-2 exists as a non-disulfide-linked homodimer which could alloweach Syk molecule to interact with two YXXL motifs, one from each CLEC-2 monomer. © 2009 American Chemical Society.